AKTIVITAS IMUNOMODULATOR REGIMEN ISOLAT MANGOSTIN, KURKUMINOID, PIPERIN, METIL SINAMAT DAN VITAMIN C DENGAN METODE CARBON CLEREANCE - Fauzi, Novi Irwan; Herawati, Irma Erika; Sari, Nia Kurnia; Fathurrahman, Muhammad Hilmi; Firmansyah, Adang; Ferdiansyah, Rival; Ismayadi, Pupung (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
The regimen of test materials consisting of mangostin isolate, curcuminoid, piperine, methyl cinnamate, and vitamin C is combined to help increase body immunity (immunostimulant). Immunostimulant activity testing was carried out using the carbon clearance method. 30 male Wistar rats were randomly divided into 5 groups, namely the normal control group, the comparison drug control, and dose groups I, II and III where the regimen of the test material was given at consecutive doses of 7.2; 72; 720 mg /kg respectively. The treatment was given for 6 days, then a carbon suspension dose of 0.5 mL / BW was given intravenously. Blood samples from the tail vein at 5, 10, and 15 minutes were measured for absorbance using a UV-Vis spectrophotometer at a wavelength of 650 nm. Phagocytosis constant and Phagocytosis Index (IF) were determined to assess immunostimulant activity. The phagocytosis constant in the regimentation of the test material showed a faster pattern in eliminating carbon compared to the normal control group and the reference drug. The regimentation of the test material also had an IF value > 1.5 which is a strong immunostimulant category.